Parametric Optimization of Wire Electrical Discharge Machining in AA7075 Metal Matrix Composite - K. Raju; M. Balakrishnan; C. B. Priya; M. Sivachitra; Dasari Narasimha Rao (Advances in Materials Science and Engineering)
Aluminium 7075 metal matrix composite reinforced with silicon nitride was fabricated using the stir casting technique. Composite fabricated was machined and subjected to wire electrical discharge machining to study the significant process parameter. Taguchi design of experiment using L9 orthogonal array was selected with three factors, current, pulse ON time, and wire feed at three levels. Influencing process parameters were identified using analysis of variance. Pulse ON time of 130 μs, current of 20 A, and wire feed of 1 mm/min were identified as optimized parameters for higher material removal rate. For a good surface finish, the optimized parameter was identified as 130 μs pulse ON time, 20 A current, and wire feed rate of 2 mm/min. Pulse ON time was identified as an influencing parameter followed by the current in achieving better material removal rate with good surface finish, whereas wire feed has no influence on the output parameters. Results of experimentation showed improved machining characteristics for higher pulse ON time and current for machining the synthesized composite through the Taguchi design of the experiment.